Ameliorating effects of low-dose ketamine administrations on opioid-induced memory impairments and neurodegeneration in mice - Uyar, Emre; Seker, Ugur; Ozhan, Onural; Acikgul, Muhammet Burak; Colak, Mehmet; Izci, Sevde Feyza; Parlakpinar, Hakan (Annals of Medical Research, 2023)
Aim: Opioids have indispensable roles in pain management. A strong link exists between opioid use and memory impairments, mainly with continuous use. This study investigated the effects of two opioid drugs, meperidine and fentanyl, on emotional memory functions, brain morphology, and the possible protective effects of low-dose ketamine in mice.Materials and Methods: A passive avoidance (PA) test was used to measure emotional memory functions following seven daily drug applications in 48 male Balb/C mice (30-35 g). Meperidine (10 mg/kg), fentanyl (0.3 mg/kg), ketamine (5 mg/kg), and combinations of ketamine with the opioids were intraperitoneally injected daily. No drugs were utilized during the testing days. Brain tissues were obtained after sacrification and put into diluted formalin solution for histopathological analysis.Results: Transfer latencies of the meperidine and fentanyl-treated groups in the PA test were lower than in the vehicle-treated group (p
Keywords: Ketamine; Opioids; Memory impairments; Passive avoidance; Brain morphology